Lying, Deceptive Implicatures, and Commitment - Alexander Wiegmann; Jörg Meibauer; Pascale Willemsen (Ergo, An Open Access Journal of Philosophy)
Deceptive implicatures are a subtle communicative device for leading someone into a false belief. However, it is widely accepted that deceiving by means of deceptive implicature does not amount to lying. In this paper, we put this claim to the empirical test and present evidence that the traditional definition of lying might be too narrow to capture the folk concept of lying. Four hundred participants were presented with fourteen vignettes containing utterances that communicate conversational implicatures which the speaker believes to be false. We further collected several potential proxy measures of lying, to get a better understanding of when a deceptive implicature is considered a case of lying. The results indicate that most implicatures (ten out of fourteen) were evaluated as lies and that lie ratings were closely tracked by the degree to which speakers were considered to have committed themselves to the truth of the content conveyed by their deceptive implicatures.